Penerapan Media Interaktif Wordwall dalam Proses Pembelajaran di SMPN 1 Pekanbaru - Fitri Hasanah; Elsi Aulia; Esti Raihana (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
The use of technology-based learning media is believed to increase effectiveness and attractiveness in the learning process. One of the potential media to be implemented is Wordwall, an interactive platform that provides various types of educational games to support learning. This activity aims to increase student motivation and cooperation through the application of Wordwall media in mathematics learning, especially in arithmetic function material at SMPN 1 Pekanbaru. The method used in this activity consists of two stages, namely the preparation stage and the learning stage. In the preparation stage, the team designs activities and prepares teaching materials. Furthermore, in the learning stage, Wordwall media is applied in the learning process, including through interactive quizzes that actively involve students. The results of the activity show that the use of Wordwall can increase student involvement in learning, as well as create a more interactive and enjoyable learning atmosphere. Thus, Wordwall media can be an effective alternative in increasing student motivation and learning outcomes.